EFFORTS TO INCREASE LEARNING MOTIVATION AND RESILIENCE OF PTM/A STUDENTS DURING THE COVID-19 PANDEMIC USING ISLAMIC NEURO LINGUISTIC PROGRAMMING - Haq, Akhmad Liana Amrul; Rohmadani, Zahro Varisna (Psikis : Jurnal Psikologi Islami, 2023)
This study aimed to determine the effectiveness of Islamic Neurol Linguistic Programming (INLP) techniques in increasing student motivation and resilience. The subjects of this study were students at PTMA (Muhammadiyah-Aisyiyah Higher Education Institutions) in Indonesia. A two-group pretest-posttest experimental design was used, where all research subjects were divided into two treatment groups: the experimental group and the control group. Data collection was measured by using 2 measuring instruments, namely the learning motivation scale and the resilience scale to measure the differences between conditions at the pretest and posttest. This research aimed to provide a practical solution to enhance the learning motivation and resilience of PTMA students during the covid-19 pandemic so that the subjects would be psychologically healthier. The data collected in this study used the Resilience and Motivation scale. Based on statistical tests, it was found that Islamic Neuro Linguistic Programming (INLP) can increase student resilience and learning motivation because INLP is a form of an applicable practical intervention that can be used during daily worship.